Rehabilitation Process Issues and Functional Performance after Total Hip and Knee Replacement - Fedonnikov, Alexander S.; Andriyanova, Elena A.; Kiselev, Anton R.; Norkin, Igor A. (Healthcare (Basel), 2021)
(1) Background: to ensure satisfactory outcomes in patients who have undergone total hip or knee replacement, it is crucial to prioritize postoperative rehabilitation process and its management rather than the successful surgery alone. The goal of our study was to investigate the outcomes of rehabilitation process after the total hip or knee replacement, including local orthopedic follow-up, communication with local health authorities, patients’ satisfaction regarding rehabilitation, and their functional performance after the surgery. (2) Methods: the study included 523 patients who underwent total hip replacement, and 650 patients who underwent total knee replacement. All patients were surveyed via formalized phone interviews containing questions related to postoperative rehabilitation parameters and outcomes. (3) Results: in postsurgical period, nearly 70% of patients had regular local orthopedic follow-up. Lack of the latter at the local level was indicated by approximately 10% of patients, and the rest of the respondents note the practice of sporadic follow-up. Half of patients reported pains of various severity. Good physical activity (e.g., ability to walk unassisted within their residential district) was acknowledged by about a quarter of patients. Ability to walk unassisted was reported by just 54.5% of patients. (4) Conclusions: the disproportion between generally high patient satisfaction of rehabilitation management (>80%) and low feedback level on the part of local health authorities (9.4%) demonstrated lack of communication between the key parties involved in the rehabilitation process.